Investigation of the degradations in power GaN-on-Si MIS-HEMTs subjected to cumulative γ-ray irradiation. (September 2019) - Sharma, Chandan; Modolo, Nicola; Chen, Hsi-Han; Tseng, Yang-Yan; Tang, Shun-Wei; Meneghini, Matteo; Meneghesso, Gaudenzio; Zanoni, Enrico; Singh, Rajendra; Wu, Tian-Li
Abstract: In this work, GaN-on-Si power Metal-Insulator-Semiconductor High Electron Mobility Transistors (MIS-HEMTs) are irradiated through different regimes of cumulative γ -ray irradiation, namely 1, 2, 3, 4, and 5 kGy for the first sample; 1, 3, and 5 kGy for the second sample; 1, 5, and 10 kGy for the third sample; and 1, 10, and 20 kGy for the fourth sample. After each irradiation dose, drain current (ID ), threshold voltage (VTh ), and gate leakage current (Ig ) are electrically characterized in all the samples. An improvement in ID with a shift in VTh is observed in all the samples, which saturates after a higher irradiation dose. X-ray photoelectron spectroscopy (XPS) analysis confirms creation of nitrogen vacancies that act as donor and improves the ID . No significant change in Ig is observed except for an increase in noise in gate leakage current. Scanning electron microscopy (SEM) shows the Al-based metallization pad degrades due to formation of small cavities. Finally, energy dispersive X-ray (EDX) analysis confirms the formation of Al native oxides due to γ -ray irradiation.